Circadian rhythms as modulators of brain health during development and throughout aging - Van Drunen, Rachel; Eckel-Mahan, Kristin (Frontiers in Neural Circuits, 2023)
The circadian clock plays a prominent role in neurons during development and throughout aging. This review covers topics pertinent to the role of 24-hr. rhythms in neuronal development and function, and their tendency to decline with aging. Pharmacological or behavioral modification that augment the function of our internal clock may be central to decline of cognitive disease and to future chronotherapy for aging-related diseases of the central nervous system.